New treatment insights into pancreatic acinar cell carcinoma: case report and literature review - Zhao, Fangrui; Yang, Dashuai; Xu, Tangpeng; He, Jiahui; Guo, Jin; Li, Xiangpan (Frontiers in Oncology, 2023)
Pancreatic acinar cell carcinoma (PACC) is a rare pancreatic malignancy with unique clinical, molecular, and morphologic features. The long-term survival of patients with PACC is substantially better than that of patients with ductal adenocarcinoma of the pancreas. Surgical resection is considered the first choice for treatment; however, there is no standard treatment option for patients with inoperable disease. The patient with metastatic PACC reported herein survived for more than 5 years with various treatments including chemotherapy, radiotherapy, antiangiogenic therapy and combined immunotherapy.